A novel lignite pre-drying system integrated with flue gas waste heat recovery at lignite-fired power plants. (5th March 2019) - Yan, Min; Ma, Chunyuan; Shen, Qiuwan; Song, Zhanlong; Chang, Jingcai
Abstract: To reduce steam consumption of conventional lignite pre-drying systems, a novel system based on two-stage pre-drying was proposed in this study. In the proposed system, flue gas waste heat following wet flue gas desulphurisation (WFGD) was recovered and used as the heat source for the first pre-drying stage. Thus, the total heat required from extracted steam was significantly decreased, and electric power output was increased accordingly. Furthermore, the system could be used to recover clean water from flue gas to be utilised by WFGD. The thermodynamic and techno-economic performances of the proposed system were calculated and compared with those of a conventional system using data from a typical 600 MW lignite-fired power plant. The thermodynamic calculations showed that the net efficiency of power plants fitted with the proposed system could be increased by 1.06% points compared with that of the original unit, which was 0.3% points more than the 43.31% efficiency of the conventional system. The techno-economic analysis showed that the net annual earnings assuming a 30 y lifespan would be 4.89 million USD, which were 0.82 million USD more than the earnings using the conventional system (4.07 million USD).